EFEKTIVITAS PROGRAM ZIGMA TERHADAP PENINGKATAN PEMAHAMAN GIZI SEIMBANG PADA REMAJA DESA SUKAMERINDU - Fakhriyatiningrum Fakhriyatiningrum; Syifa Salsabila; Khanza Hikmah Anastasya; Thasya Cahya Wijaya; Depi Depi; Rahma Febrian Nurzahra; Helendari Helendari; Shafiqah Naurah Asliyah; Azzah Gandes Lituhayu; Wahyuna Wahyuna; Muhammad Faaiz Aqiilah; Sabrina Zafirah Putri; Mustika Rosfero (PARIPALAKA SRIWIJAYA, 2026)
Adolescents are an age group that is prone to various nutritional problems, both deficiency or excess, due to unbalanced diet and lack of awareness of the importance of healthy living behavior. Nutritional imbalance in adolescence can be impact on long-term growth, development, and quality of life. Based on these conditions, nutrition counseling activity were conducted to 30 adolescents in Sukamerindu village, Lubai district, Muara Enim regency, as an effort to increase the knowledge about balanced nutrition. The method that used in this activity is participatory educational through interactive lecture, group discussion, also pre-test and post-test filling. The contents that given in this counseling including the concept of diverse food consumption, balanced nutrition guidlines, the importance of consuming vegetables, fruits, protein, and water, also education about clean and healthy living behavior, with the support of media in the form of leaflets. The evaluation of results showed an increase in the average score from 60 in the pre-test to 80 in the post test, which most participants experiencing an increasement in scores. Active participation from the participants and involvement in discussion showed a high enthusiasm as well as the effectiveness of the approach that been used. The material that delivered which tailored to the characteristics of adolescents and the used of visual media proved to strengthen their understanding. The results of the activity showed that a communicative and participatory approach to community-based education has a positive impact on improving adolescent nutrition knowledge and potentials to become a long-term strategy in improving quality of public health and human resources. Keyword : Balanced nutrition, adolescents, nutrition counseling, educational intervention